A multidimensional evaluation of patients with idiopathic intracranial hypertension: associations across symptoms, imaging, cerebrospinal fluid findings and medical history - Zakirul Islam, M.; Sarkar, Mohammad Sadekur Rahman; Ahasan Ahmed, K. M.; Al Mamun, Abdullah; Merazul Islam Shaikh, M.; Losy, Sadeka Afrin; Badrul Alam, M. (International Journal of Research in Medical Sciences, 2025)
Background: Idiopathic intracranial hypertension (IIH) is a disorder characterized by elevated intracranial pressure without identifiable cause, predominantly affecting overweight women of reproductive age. Headache and visual disturbances are common but often show variable correlation with cerebrospinal fluid (CSF) pressure. This study aimed to evaluate the multidimensional associations among clinical symptoms, imaging, CSF findings and medical history in patients with IIH. Methods: This cross-sectional study was conducted at the department of neuro medicine, National Institute of Neuro Sciences and Hospital, Dhaka, Bangladesh, from July 2022 to June 2025. A total of 100 patients aged 18-50 years with a confirmed diagnosis of IIH and neuro-ophthalmic symptoms were included. Data were collected through clinical evaluation, lumbar puncture, imaging (MRI/MRV), fundal photography and visual field testing. Statistical analysis was performed using SPSS version 25.0. Results: The mean age was 26.16±7.49 years, with a strong female predominance (92%). Most patients were overweight or obese. Headache (97%), visual impairment (88%) and cranial nerve palsy (50%) were the predominant symptoms. Papilledema was bilateral in 93% of cases. Elevated CSF opening pressure (>25 cm H2O) was found in 75% of patients. Hormonal medication use was reported in 33% of cases. No significant association was observed between elevated CSF pressure and visual loss (p=0.02), double vision (p=0.96), or headache (p=0.53). Conclusions: Symptom severity in IIH may not directly correlate with CSF pressure levels, underscoring the need for comprehensive, multidisciplinary assessment in clinical management.